Peran Guru Bimbingan dan Konseling dalam Meningkatkan Self-Control Siswa Broken home - Amanda, Sesilia; Arsini, Yenti (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
This research focuses on the role of guidance and counselling teachers in improving the self-control of broken home students. In this study researchers used descriptive qualitative research methods with data collection techniques are observation, interviews conducted with 5 broken home students who have low self-control and counseling teachers of SMP Negeri 1 Peureulak Timur, and documentation. The data analysis method that researchers use is data reduction, data presentation and conclusion making and data validity testing using the source triangulation method and method triangulation. This research was conducted at SMP Negeri 1 Peureulak Timur. The results of this study obtained that the role of the Guidance and Counselling Teacher is very important in helping broken home students improve their self-control. However, the implementation of counselling activities found inhibiting factors, including the lack of support and environment from the family and limited school facilities. therefore as a counseling teacher must continue to monitor the development and solve the problems experienced by students at SMP Negeri 1 Peureulak Timur.